Análise comparativa de metodologias utilizadas no despacho de caminhões em minas a céu aberto - Lasara Fabricia Rodrigues (2006)
In the present study a comparative analysis of the methodologies used to dispatch trucks in open pit mines has bee carried out. These methodologies serve as the basis of algorithms used in the dispatch systems sold in Brazil. Linear programming and dynamic programming based methodologies as well as heuristics-based methodologies have been implemented. Simulation has been used to reproduce conditions of mining operations. Results show the performance of algorithms that have employed these methodologies under different conditions in open pit mining. It is not possible, however, to state through the results obtained in the present study the superiority of any of them.